Continuing library education: Declaration and reality - I. S. Pilko (Библиосфера, 2013)
The purpose of the article is to attract attention of educational community, researchers, practitioners and managers of libraries to the problems of preparation of library staff involved in the implementation of the competence approach to the educational process and practical activity.